O direito dos povos indígenas à educação superior na América Latina : concepções, controvérsias e propostas - Gaivizzo, Soledad Bech (2014)
The public debate on indigenous higher education, guided by a human rights perspective, keeps on gaining visibility with the construction of an international legal framework for the promotion and specific protection of indigenous people. Regarding the Latin American public scene, from this framework on comes a set of propositions, inspired by different theoretical nuances, to ensure the right of these people to higher education. In short, these rights were chosen as the focal point of this investigation. The main objective is to investigate how to ensure indigenous people higher education in Latin American countries, taking into account the institutionalization of the international legal framework, which broadened the understanding of the topic and specified forms to materialize it in society. Having these issues in mind, the adopted method of research is defined in terms of analyzing the right of indigenous people to higher education according to the Decoloniality theory, which is the school of thought that analyzes racial-ethnic relations in society and in education. For this matter both the discourses of social actors participating in this debate (with the classification criteria of ethnic belonging, indigenous and non-indigenous) and the representation of social actors (representatives of the state and the surrounding segments of both the established and the indigenous societies) were considered. An approach of qualitative and of technical generation of data for the textual analysis of the discourse were used.